Data analysis on the Bangladesh share market using Machine-Learning - Sadman, Syed Hassan; Rahat, Hasib Al; Hamim, Atikur Rahman; Al Kafi, Sultan Gias Uddin; Khan, Nasik Ali (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.